The role of preoperative PSA level in prostate cancer - Dere, Yelda; Akarken, İlker; Şahin, Hayrettin (International Journal of Advances in Medicine, 2018)
Background: PSA levels between 0-4 ng/ml is generally accepted as normal range, there is no world widely accepted cut-off value. PSA level is most commonly used for determining patients to whom needle biopsy should be performed. Authors aimed to investigate the relationship between preoperative PSA level and histopathological features. Methods: Ninety prostatic adenocarcinoma cases diagnosed between January 2013 and January 2018 and treated by RP were included. Patients had no measurement of PSA before the operation were excluded from the study. Patients were grouped according to preoperative PSA as low-risk (<10 ng/ml), medium-risk (10-20 ng/ml) and high-risk (>20 ng/ml). The relations between all of the histopathological parameters were analyzed in addition to the preoperative PSA levels. Results: The mean age and preoperative PSA level was found as 64.16, and 12.33, respectively. The presence of EPE and tumour positive base margin showed significant relation among PSA groups as well as the presence of lymphovascular invasion and the involvement of the seminal vesicles. Intracytoplasmic mucin and foamy cytoplasm was more common in low-risk PSA group and the difference was significant. Conclusions: PSA level is one of the most commonly used marker for predicting high risk patients before the operation however it may also show relation with various histopathological factors that have effect on the prognosis of prostatic adenocarcinoma.